(untitled) (Philology, 2023)
The text reflects on the dynamic changes that have occurred in the makeup and rationale of English Studies associated majors on offer at Plovdiv University Paisii Hilendarski (PU) as revealed through the views of students enrolled in three distinctive strands of programs. The contours of these developments are addressed by comparing cohorts of ES students at PU across time. Namely, the discussion relies on a comprehensive student survey that registered students’ views in 2008 and 2018, i.e. with a time lapse of a decade, against the background of broader contextual developments and narrowly institutional such (PU institutional policies) in the interim period. Within the institutional context of PU, the developments amount to diversifying the portfolio of BA degree options from traditionally philologically-oriented such to those following an applied linguistics model on one hand, and majors involving a degree of interdisciplinary “hybridization” on the other. These transformations appear further nuanced with a view to the distinctive features that come across the responses of three qualitatively different student cohorts. One, those pursuing ES degrees within a more conventional philological model; two, those engaged in ES related degrees following an Applied Linguistics model; and finally, those who study ES as a component in combinations with IT, Marketing and Business Administration. Even if limited to the institutional context of PU, the survey offers scope for considering the implications for the HE philological horizons of foreign language education from the perspective of the changing expectations, attitudes and career aspirations of the undergraduates involved in them.